2017
DOI: 10.1002/er.3733
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic tank in series modeling of direct internal reforming SOFC

Abstract: Summary A dynamic tank in series reactor model of a direct internally reforming solid oxide fuel cell is presented and validated using experimental data as well as a computational fluid dynamics (CFD) model for the spatial profiles. The effect of the flow distribution pattern at the inlet manifold on the cell performance is studied with this model. The tank in series reactor model provides a reasonable understanding of the spatio‐temporal distribution of the key parameters at a much lesser computational cost w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In addition, a higher overpotential is obtained due to the slow kinetics of the CO/CO 2 electrochemical reaction, but the experimental results show that the I‐V curves for pure H 2 O and syngas with low H 2 O and high CO 2 are almost identical. These results indicate that the WGS reaction is the preferred pathway for CO/CO 2 consumption in co‐redox reactions in SOFCs and SOECs . Hauck et al compared simulation results with experimental data and concluded that the best fit is obtained when CO/CO 2 is only considered in the WGS reaction when syngas is provided to an rSOFC.…”
Section: Model Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, a higher overpotential is obtained due to the slow kinetics of the CO/CO 2 electrochemical reaction, but the experimental results show that the I‐V curves for pure H 2 O and syngas with low H 2 O and high CO 2 are almost identical. These results indicate that the WGS reaction is the preferred pathway for CO/CO 2 consumption in co‐redox reactions in SOFCs and SOECs . Hauck et al compared simulation results with experimental data and concluded that the best fit is obtained when CO/CO 2 is only considered in the WGS reaction when syngas is provided to an rSOFC.…”
Section: Model Descriptionmentioning
confidence: 99%
“…39 In addition, dynamic switching is also modeled to investigate the switching performance between an SOFC and an SOEC. 38,39,[46][47][48][49] On the other hand, most of the dual-mode investigations presented above are focused on H 2 /H 2 O. The coredox reactions with syngas are mostly presented in a single FC or EC mode.…”
Section: The Strategy Of Operation In Dual-modementioning
confidence: 99%
See 2 more Smart Citations
“…However, this involves the trade-offs of reduced cell average temperature and reduced fuel utilisation, which are not desirable. A novel design for the planar SOFC interconnect was proposed by us in [18] to reduce the excessive thermal gradients. This design tackles the problem by introducing a secondary air stream in the counter direction and orifice based localised cooling to even out temperature differences and reduce hot spots.…”
Section: 12planar Sofc Thermal Managementmentioning
confidence: 99%